Extending broadband's reach. - Riezenman, M.J (IEEE spectrum)
Private companies and standards bodies are straining to somehow boost the performance of the two chief last-mile broadband technologies: digital subscriber lines (DSLs), which send data over telephone wires, and cable modems, which use TV cables. A further extension of ADSL2, known as ADS L2+ and also expected to win ITU approval, promises to double the data rates of today's technology to 25 Mb/s in the best of circumstances.